Homo Clausus, Homo Sacer, Homines Aperti: Challenges for Group Analysis in the 21st-Century. A Response to Haim Weinberg's 40th Foulkes Lecture. (December 2016) - Penna, Carla
In this response I will bring the historical roots of the modern individualism and Norbert Elias conceptualizations on Homo Clausus and Homines Aperti—also introducing as Agamben's discussion on Homo Sacer and other forms of human and societal prejudice and exclusion—to criticize contemporary individualism and discuss the challenges for group analysis in the 21st-century. I build on Haim Weinberg's concerns on 'Impossible groups that Flourish in Leaking Containers' to highlight the importance of 'total situations' and 'applied' group analysis, since 1948 Foulkes tenets until the current group analytic new challenges.